2016
DOI: 10.22436/jnsa.009.06.47
|View full text |Cite
|
Sign up to set email alerts
|

On strong intuitionistic fuzzy metrics

Abstract: In this paper we give some properties of a class of intuitionistic fuzzy metrics which is called strong. This new class includes the class of stationary intuitionistic fuzzy metrics. So we examine the relationship between strong intuitionistic fuzzy metric and stationary intuitionistic fuzzy metric.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…He showed that for each intuitionistic fuzzy metric space (X, M, N, * , ♦), the topology generated by the intuitionistic fuzzy metric (M, N ) coincides with the topology generated by the fuzzy metric M . For more details on intuitionistic fuzzy metric space and related results we refer the reader to [2,7,9,13,19,[21][22][23]27]. In 2006, Saadati and Park introduced the notion of intuitionistic fuzzy normed space [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He showed that for each intuitionistic fuzzy metric space (X, M, N, * , ♦), the topology generated by the intuitionistic fuzzy metric (M, N ) coincides with the topology generated by the fuzzy metric M . For more details on intuitionistic fuzzy metric space and related results we refer the reader to [2,7,9,13,19,[21][22][23]27]. In 2006, Saadati and Park introduced the notion of intuitionistic fuzzy normed space [25].…”
Section: Introductionmentioning
confidence: 99%
“…for any a, b ∈ [0, 1]. Now we recall the definitions of intuitionistic fuzzy metric space which was introduced by Park [21] in 2004 (see also [9]).…”
Section: Introductionmentioning
confidence: 99%